Numerical investigation of vortex induced rotation of two square cylinders in tandem arrangement. (1st January 2019) - Shao, J.Y.; Shu, C.; Liu, N.Y.; Zhao, X.
Abstract: This work performs a numerical investigation on the dynamics of the system with two square cylinders arranged in tandem at Reynolds number of 100. The influence of the vortex induced rotation and the spacing ratio (center-to-center distance over square width) between two cylinders is studied. Four system setups are considered. Case 1: Two stationary square cylinders in tandem; Case 2: Only the trailing square cylinder is allowed to rotate around its axis; Case 3: Only the leading square cylinder is allowed to rotate and Case 4: Both square cylinders are allowed to rotate around their own axes respectively. It shows that both the system setup and the spacing ratio can have significant influence on the dynamics of the system. When the leading cylinder is fixed, as in Case 1 and Case 2, the spacing ratio has the dominant effect. In these two cases, it can be very effective to suppress C d m e a n / C l r m s (mean drag coefficient/root mean square of lift coefficient) by keeping the spacing ratio below the critical value. In contrast, allowing the leading cylinder to rotate freely as in Case 3 and Case 4, changes the baseline of the dynamics of the system. It triggers formation of vortex shedding in the gap region with a smaller critical spacing ratio, compared with cases having a fixed leading cylinder. The force fluctuations and rotational amplitude are also much larger than those in Case 1 and Case 2. More complex flow patterns and interactions can be observed in these cases as well. It can be concluded that, keeping the leading cylinder stationary is crucial to suppress force fluctuations of the system under the conditions studied in this paper (at the Reynolds number of 100, ξ = 0, U θ = 10 and I = 1 ).